Gravure‐Printed Flexible Perovskite Solar Cells: Toward Roll‐to‐Roll Manufacturing - Kim, Young Yun (Adv Sci (Weinh), 2019)
Recent advances in perovskite solar cells (PSCs) have resulted in greater than 23% efficiency with superior advantages such as flexibility and solution‐processability, allowing PSCs to be fabricated by a high‐throughput and low‐cost roll‐to‐roll (R2R) process. The development of scalable deposition processes is crucial to realize R2R production of flexible PSCs. Gravure printing is a promising candidate with the benefit of direct printing of the desired layer with arbitrary shape and size by using the R2R process. Here, flexible PSCs are fabricated by gravure printing. Printing inks and processing parameters are optimized to obtain smooth and uniform films. SnO(2) nanoparticles are uniformly printed by reducing surface tension. Perovskite layers are successfully formed by optimizing the printing parameters and subsequent antisolvent bathing. 2,2′,7,7′‐Tetrakis‐(N,N‐di‐4‐methoxyphenylamino)‐9,9′‐spirobifluorene is also successfully printed. The all‐gravure‐printed device exhibits 17.2% champion efficiency, with 15.5% maximum power point tracking efficiency for 1000 s. Gravure‐printed flexible PSCs based on a two‐step deposition of perovskite layer are also demonstrated. Furthermore, a R2R process based on the gravure printing is demonstrated. The champion efficiency of 9.7% is achieved for partly R2R‐processed PSCs based on a two‐step fabrication of the perovskite layer.